Comparative analysis of infectious complications with outpatient vs. inpatient care for adults with high-risk myeloid neoplasm receiving intensive induction chemotherapy. Issue 1 (2nd January 2022) - Halpern, Anna B.; Othus, Megan; Howard, Nicholas P.; Hendrie, Paul C.; Percival, Mary-Elizabeth M.; Hartley, Garrett A.; Welch, Verna L.; Estey, Elihu H.; Walter, Roland B.
Abstract: We recently reported an early hospital discharge (EHD) care strategy following intensive acute myeloid leukemia (AML)-like chemotherapy is safe. To evaluate its impact on infectious outcomes, we compared all adults treated from 8/1/2014 to 7/31/2018 discharging within 72 h of completing chemotherapy (EHD) with hospitalized patients (controls) across 354 induction and 259 post-remission cycles. While overall outcomes were similar, gram-positive bacteremias were more common in EHD patients than control ( p <.001), although they received fewer days of IV antimicrobials ( p < .001). Notably, cumulative infection risks in EHD patients were similar after induction and post-remission therapy. In multivariable analysis, only EHD status was independently associated with risk for gram-positive bacteremia ( p = .01), whereas the only independent risk factor for fungal infection was fluconazole ( vs. posaconazole) use ( p < .001). The observation of increased rates of gram-positive bacteremias with EHD identifies improvements in catheter management as one area to further increase the safety of this care approach.